1943
DOI: 10.1002/ar.1090850102
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropic activity of the pituitary gland in relation to the seasonal sexual cycle of the cottontail rabbit (Sylvilagus floridanus Mearnsi)

Abstract: FOUR FIGURESThe purpose of this work was to investigate the reproductive cycle of a non-hibernating wild mammal. The cottontail rabbit (Sylvilagus floridanus mearnsi Allen) was selected for this study because it is an abundant species of wide occurrence and of great economic importance. The weight changes in the endocrine glands directly related to the breeding cycle and the changes in the accessory reproductive organs of both male and female cottontail rabbits have been followed throughout the year t,o determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
8
0

Year Published

1951
1951
1992
1992

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 15 publications
3
8
0
Order By: Relevance
“…The shape of the weight curve for the testes found in this study of the muskrat agrees quite well with that found by Elder and Finerty (1943) for the cottontail rabbit. These both contrast with that found by Wells (1935) in the thirteenlined ground squirrel, as the peak testes weights for the muskrat and cottontail rabbit I1re maintained for a considerable period of time, while the peak testes weights for the thirteen-lined ground squirrel are held for a very short period.…”
Section: Adsupporting
confidence: 89%
See 1 more Smart Citation
“…The shape of the weight curve for the testes found in this study of the muskrat agrees quite well with that found by Elder and Finerty (1943) for the cottontail rabbit. These both contrast with that found by Wells (1935) in the thirteenlined ground squirrel, as the peak testes weights for the muskrat and cottontail rabbit I1re maintained for a considerable period of time, while the peak testes weights for the thirteen-lined ground squirrel are held for a very short period.…”
Section: Adsupporting
confidence: 89%
“…This was also found in the cottontail rabbit by Elder and Finerty (1943). The activity of the immature female muskrat was quite irregular while the immature males show an even, low activity.…”
Section: Adsupporting
confidence: 54%
“…Seasonal changes in concentration of testosterone and gonadotrophin, testicular size and fec¬ undity have been well documented in wild rabbits (Elder & Finerty, 1943;Davis & Meyer, 1973a;Lincoln, 1976;Boyd & Myhill, 1987). Gonadotrophin concentrations increase with testicular weight during the spring and summer and decline during the autumn, reaching minimum values at about the winter solstice.…”
Section: Introductionmentioning
confidence: 99%
“…At the onset of the main breeding season in the autumn there is a great increase in the size and activity of the prostate which averages a sixfold increase in weight (Gilmore, 1968). The size of the testes does not alter significantly during the year, but there is a marked stimulation of the interstitial tissue in the autumn.Changes in the pituitary gonadotrophin content in seasonal breeding animals have been observed (see Elder & Finerty, 1943;Swift & Pickford, 1965). In contrast Hutchinson & Robertson (1960) found no changes in the ewe.…”
mentioning
confidence: 99%
“…Changes in the pituitary gonadotrophin content in seasonal breeding animals have been observed (see Elder & Finerty, 1943;Swift & Pickford, 1965). In contrast Hutchinson & Robertson (1960) found no changes in the ewe.…”
mentioning
confidence: 99%